Microbicidal effects of α- and θ-defensins against antibiotic-resistant Staphylococcus aureus and Pseudomonas aeruginosa. Issue 1 (January 2015) - Tai, Kenneth P; Kamdar, Karishma; Yamaki, Jason; Le, Valerie V; Tran, Dat; Tran, Patti; Selsted, Michael E; Ouellette, André J; Wong-Beringer, Annie
Antibiotic-resistant bacterial pathogens threaten public health. Because many antibiotics target specific bacterial enzymes or reactions, corresponding genes may mutate under selection and lead to antibiotic resistance. Accordingly, antimicrobials that selectively target overall microbial cell integrity may offer alternative approaches to therapeutic design. Naturally occurring mammalian α- and θ-defensins are potent, non-toxic microbicides that may be useful for treating infections by antibiotic-resistant pathogens because certain defensin peptides disrupt bacterial, but not mammalian, cell membranes. To test this concept, clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA), including vancomycin heteroresistant strains, and ciprofloxacin-resistant Pseudomonas aeruginosa (Cip R -PA) were tested for sensitivity to α-defensins Crp-4, RMAD-4 and HNPs 1-3, and to RTD-1, macaque θ-defensin-1. In vitro, 3 μM Crp-4, RMAD-4 and RTD-1 reduced MRSA cell survival by 99%, regardless of vancomycin susceptibility. For PA clinical isolates that differ in fluoroquinolone resistance and virulence phenotype, peptide efficacy was independent of strain ciprofloxacin resistance, site of isolation or virulence factor expression. Thus, Crp-4, RMAD-4 and RTD-1 are effective in vitro antimicrobials against clinical isolates of MRSA and Cip R -PA, perhaps providing templates for development of α- and θ-defensin-based microbicides against antibiotic resistant or virulent infectious agents.